Influence of theoretical and practical artificial intelligence knowledge on the primary school teachers’ sustainable AI integration ability: mediating effects of beliefs and attitudes - Kazmaci, Aytun; Cek, Kemal; Altinay, Fahriye; Altinay, Zehra; Dagli, Gokmen (Frontiers in Psychology, 2025)
Artificial intelligence (AI) has great potential to be integrated into education to improve teaching and learning practices. However, the attainment of effective and sustainable AI tools usage in the primary education of the teachers’ knowledge, beliefs, and attitudes is critical. This study examines the impact of theoretical and practical AI knowledge on the sustainable integration of AI in primary school classrooms, with a focus on the mediating role of teachers’ beliefs and attitudes. A structured questionnaire was used to collect data from 340 primary school teachers in Northern Cyprus. Structural Equation Modeling (SEM) was used to test the relationships between AI knowledge, beliefs and attitudes and sustainable AI integration. Findings indicate that both theoretical and practical AI knowledge indirectly contribute to the integration of AI. Specifically, the beliefs and attitudes of teachers toward AI are a critical mediator that maintains the relationship. The results underscore the importance of training teachers to enhance their understanding of AI, cultivate positive attitudes, and boost their confidence in AI technologies. To offer better strategies that enhance the sustainable integration of AI in primary education, educational policymakers and institutions must consider these psychological factors that need to be addressed. This research contributes to the emerging body of work on AI in education, in general, and the interplay between knowledge, attitudes, and AI adoption, in particular, emphasizing the need for a holistic strategy toward teacher development.